Preparation method of high-ultraviolet-transmittance 193nm film
By alternately plating the lanthanum fluoride and magnesium fluoride films on the surface of ultraviolet fused silica and annealing under a fluorine atmosphere, and applying ultraviolet light irradiation, the problems of structural relaxation and poor environmental stability of the 193nm fluoride film were solved, and a high-transmissive ultraviolet 193nm film with high light transmission and high density were achieved.
Patent Information
- Application Number
- CN202411788318.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art has problems of structural relaxation and poor environmental stability when preparing 193nm fluoride films, which are difficult to meet the needs of high light transmission and high density.
The vacuum coating method was used to alternately plate four layers of lanthanum fluoride and magnesium fluoride film on the surface of ultraviolet fused silica, and annealed under a fluorine atmosphere. Ultraviolet light was applied during annealing to improve the density and adhesion of the film.
The high light transmittance and density of the high-transmissive ultraviolet 193nm film is achieved, the structural stability of the film and the bonding strength with the substrate are improved, and the problems of structural relaxation and poor environmental stability are solved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical films, and in particular to a method for preparing a high-transmittance ultraviolet 193nm film. Background Art
[0002] With the application of lasers in the semiconductor industry, optical films are required to have high performance and stability in the short wavelength range. In particular, optical films in ArF laser systems are of great significance for laser micromachining and lithography technology.
[0003] .Vacuum coating equipment mainly refers to a type of coating that needs to be carried out under a higher vacuum degree. It includes many types, including vacuum resistance heating evaporation, electron gun heating evaporation, magnetron sputtering, MBE molecular beam epitaxy, PLD laser sputtering deposition, ion beam sputtering and many other types.
[0004] The rapid development of my country's optical film industry has led to an increasing demand for 193nm anti-reflection film lenses used in lithography systems, and higher quality requirements, which has also put forward higher requirements for the preparation technology of extreme ultraviolet films. For 193nm fluoride film systems, thermal evaporation technology can obtain fluoride films with excellent stoichiometric ratios, but there are disadvantages such as structural looseness and poor environmental stability. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a high-transmittance ultraviolet 193nm film to solve the problems existing in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a high-transmittance ultraviolet 193nm film, comprising the following preparation steps:
[0007] (1) Preparation of substrate;
[0008] (2) Coating:
[0009] A. Pump the machine to a vacuum degree of 5.0~5..5×10 -3 Pa, 390-410℃ constant temperature for 3.5-4h, then lanthanum fluoride and magnesium fluoride coating, four layers of coating in sequence;
[0010] B. After coating, annealing is performed in a fluorine atmosphere, and ultraviolet light is applied during annealing to obtain a lens;
[0011] (3) The lenses are cleaned with organic solvents and then vacuum packed.
[0012] Furthermore, the preparation of the substrate in step (1) comprises the following steps:
[0013] a. Select UV grade fused silica JGS1 as the substrate;
[0014] b. Remove dirt and dust from the substrate surface before coating;
[0015] c. After the substrate is cleaned, it is heated to 400℃ in the machine.
[0016] Furthermore, the surface of the substrate is cleaned by ultrasonic cleaning or manual wiping, with ether being used as the ultrasonic solvent, for 15 minutes.
[0017] Furthermore, the power of the ultrasonic cleaning is 300-500W, and the ultrasonic frequency is 20kHz.
[0018] Furthermore, in step (2), the structures of the four-layer coating are 1.63H, 1.4121L, 0.833H, and 0.9081L in the order of coating, wherein H is lanthanum fluoride and L is magnesium fluoride.
[0019] Furthermore, in the step (2), the bombardment voltage during the coating is 800 to 820 V negative high voltage, and the bombardment time for each layer of film is 10 to 15 minutes.
[0020] Furthermore, in step (2), the flow rate of the fluorine gas atmosphere is 30 to 40 Nm3 / h.
[0021] Furthermore, the annealing in step (2) is a secondary annealing, wherein the temperature of the primary annealing is 30-35° C., the time is 8-13 min, and the temperature of the secondary annealing is 80-85° C., the time is 25-30 min.
[0022] Furthermore, in step (2), the ultraviolet light irradiation is performed using ultraviolet light with wavelengths of 185 nm and 254 nm until the annealing is completed.
[0023] Furthermore, the organic solvent in step (3) is a mixture of acetone and methanol in a mass ratio of 1:1.
[0024] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0025] The present invention provides a method for preparing a high-transmittance ultraviolet 193nm film, which effectively increases the compactness and adhesion of the high-transmittance ultraviolet 193nm film on the basis of achieving high light transmittance, thereby forming a multifunctional high-transmittance ultraviolet 193nm film.
[0026] First, four layers of lanthanum fluoride and magnesium fluoride films are alternately deposited on the surface of ultraviolet fused quartz by vacuum coating method, and then annealed in fluorine gas atmosphere. The presence of fluorine gas can make up for the problem of insufficient fluorine element in fluoride film. Annealing can release the internal stress inside the high-transmittance ultraviolet 193nm film, thereby reducing the stress level of the high-transmittance ultraviolet 193nm film, making up for the shortcomings of structural relaxation and poor environmental stability between the four layers of film, improving its structural stability, and improving its bonding strength with ultraviolet fused quartz; secondly, annealing When ultraviolet light is applied externally, annealing and ultraviolet radiation will provide sufficient energy for the lanthanum fluoride and magnesium fluoride atoms in the high-transmittance ultraviolet 193nm film to migrate and rearrange, thereby filling the gaps and defects in the film and increasing the density of the film. At the same time, ultraviolet light will optimize the microstructure and electronic state of the high-transmittance ultraviolet 193nm film, slow down the adsorption of water molecules and organic molecular groups by the film, further improve the density of the high-transmittance ultraviolet 193nm film, and increase the surface transmittance of the high-transmittance ultraviolet 193nm film and make it evenly distributed. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0028] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the high-transmittance UV 193nm film prepared in the following examples are as follows:
[0029] Light transmittance: The high-transmittance UV 193nm films of the same area prepared in the embodiment and the comparative example were tested for light transmittance and reflectance using a spectrophotometer in accordance with GB / T7962.17-2010 "Test methods for colorless optical glass Part 17: Ultraviolet and infrared refractive index".
[0030] Adhesion: According to the method of GB / T5210-2006 / IDT "Adhesion Test of Paint and Varnish by Pull-off Method", the high-transmittance UV 193nm films of the same area prepared in the embodiment and the comparative example were adhered to the coating surface with a 1-inch wide 3M special tape, and then quickly pulled up in the vertical direction of the film surface. After repeatedly pulling 20 times, the film shedding condition was tested.
[0031] Example 1
[0032] A method for preparing a high-transmittance ultraviolet 193nm film comprises the following preparation steps:
[0033] (1) Preparation of substrate:
[0034] a. Select UV grade fused silica JGS1 as the substrate;
[0035] b. Remove dirt and dust from the substrate surface before coating;
[0036] c. The surface of the substrate is cleaned by ultrasonic cleaning or manual wiping. Ether is used as the ultrasonic solvent. The power of ultrasonic cleaning is 300W, the frequency of ultrasonic cleaning is 20kHz, and the cleaning time is 15 minutes. After the substrate is cleaned, it is heated to 400℃ in the machine.
[0037] (2) Coating:
[0038] A. Pump the machine down to a vacuum degree of 5.0×10 -3 Pa, 390℃ constant temperature for 3.5h, then lanthanum fluoride and magnesium fluoride coating, four layers of coating in sequence, the bombardment voltage during coating is 800V negative high voltage, the bombardment time of each layer of film is 10min, the structure of the four-layer coating is 1.63H, 1.4121L, 0.833H, 0.9081L in the order of coating, where H is lanthanum fluoride and L is magnesium fluoride;
[0039] B. After coating, at a flow rate of 30Nm 3 / h is fluorine gas atmosphere, annealing is performed, the annealing is a secondary annealing, the temperature of the primary annealing is 30°C, the time is 8 minutes, the temperature of the secondary annealing is 80°C, the time is 25 minutes, ultraviolet light is applied during annealing, ultraviolet light with wavelengths of 185nm and 254nm is used to irradiate until the annealing is completed to obtain a lens;
[0040] (3) The lenses are cleaned with an organic solvent having a mass ratio of acetone to methanol of 1:1 and then vacuum packed.
[0041] Example 2
[0042] A method for preparing a high-transmittance ultraviolet 193nm film comprises the following preparation steps:
[0043] (1) Preparation of substrate:
[0044] a. Select UV grade fused silica JGS1 as the substrate;
[0045] b. Remove dirt and dust from the substrate surface before coating;
[0046] c. The surface of the substrate is cleaned by ultrasonic cleaning or manual wiping. Ether is used as the ultrasonic solvent. The power of ultrasonic cleaning is 400W, the ultrasonic frequency is 20kHz, and the cleaning time is 15 minutes. After the substrate is cleaned, it is heated to 400℃ in the machine.
[0047] (2) Coating:
[0048] A. Pump the machine down to a vacuum of 5.3×10 -3 Pa, 400℃ constant temperature for 3.8h, then lanthanum fluoride and magnesium fluoride coating, four layers of coating in sequence, the bombardment voltage during coating is 810V negative high voltage, the bombardment time of each layer of film is 13min, the structure of the four-layer coating is 1.63H, 1.4121L, 0.833H, 0.9081L in the order of coating, where H is lanthanum fluoride and L is magnesium fluoride;
[0049] B. After coating, at a flow rate of 35Nm 3 / h is fluorine gas atmosphere, annealing is performed, the annealing is a secondary annealing, the temperature of the primary annealing is 33°C, the time is 10 minutes, the temperature of the secondary annealing is 83°C, the time is 28 minutes, ultraviolet light is applied during annealing, ultraviolet light with wavelengths of 185nm and 254nm is used to irradiate until the annealing is completed to obtain a lens;
[0050] (3) The lenses are cleaned with an organic solvent having a mass ratio of acetone to methanol of 1:1 and then vacuum packed.
[0051] Example 3
[0052] A method for preparing a high-transmittance ultraviolet 193nm film comprises the following preparation steps:
[0053] (1) Preparation of substrate:
[0054] a. Select UV grade fused silica JGS1 as the substrate;
[0055] b. Remove dirt and dust from the substrate surface before coating;
[0056] c. The surface of the substrate is cleaned by ultrasonic cleaning or manual wiping. Ether is used as the ultrasonic solvent. The power of ultrasonic cleaning is 500W, the ultrasonic frequency is 20kHz, and the cleaning time is 15 minutes. After the substrate is cleaned, it is heated to 400℃ in the machine.
[0057] (2) Coating:
[0058] A. Pump the machine to a vacuum degree of 5..5×10 -3 Pa, 410℃ constant temperature for 4h, then lanthanum fluoride and magnesium fluoride coating, four layers of coating in sequence, the bombardment voltage during coating is 820V negative high voltage, the bombardment time of each layer of film is 15min, the structure of the four-layer coating is 1.63H, 1.4121L, 0.833H, 0.9081L in the order of coating, where H is lanthanum fluoride and L is magnesium fluoride;
[0059] B. After coating, at a flow rate of 40Nm 3 / h is fluorine gas atmosphere, annealing is performed, the annealing is a secondary annealing, the temperature of the primary annealing is 35°C, the time is 13 minutes, the temperature of the secondary annealing is 85°C, the time is 30 minutes, ultraviolet light is applied during annealing, ultraviolet light with wavelengths of 185nm and 254nm is used to irradiate until the annealing is completed to obtain a lens;
[0060] (3) The lenses are cleaned with an organic solvent having a mass ratio of acetone to methanol of 1:1 and then vacuum packed.
[0061] Comparative Example 1
[0062] The difference between Comparative Example 1 and Example 2 is that step (2) is different. Step (2) is changed to: A. Pump the machine to a vacuum degree of 5.3×10 -3 Pa, 400℃ constant temperature for 3.8h, then lanthanum fluoride and magnesium fluoride coating, four layers of coating in sequence, the bombardment voltage during coating is 810V negative high voltage, the bombardment time of each layer of film is 13min, the structure of the four-layer coating is 1.63H, 1.4121L, 0.833H, 0.9081L in sequence, where H is lanthanum fluoride and L is magnesium fluoride; B. After coating, at a flow rate of 35Nm 3 / h is a nitrogen atmosphere, and annealing is performed. The annealing is a secondary annealing. The temperature of the first annealing is 33°C and the time is 10 min. The temperature of the second annealing is 83°C and the time is 28 min. Ultraviolet light is applied during annealing. Ultraviolet light with wavelengths of 185nm and 254nm is used to irradiate until annealing is completed to obtain a lens. The remaining steps are the same as those in Example 2.
[0063] Comparative Example 2
[0064] The difference between Comparative Example 2 and Example 2 is that step (2) is different. Step (2) is changed to: A. evacuate the machine to a vacuum degree of 5.3×10 -3 Pa, 400 ° C constant temperature for 3.8h, then lanthanum fluoride and magnesium fluoride coating, four layers of coating are sequentially coated, the bombardment voltage during coating is 810V negative high voltage, the bombardment time of each film is 13min, the structure of the four-layer coating is 1.63H, 1.4121L, 0.833H, 0.9081L in the order of coating, wherein H is lanthanum fluoride and L is magnesium fluoride; B. After coating, use ultraviolet light with a wavelength of 185nm and 254nm to irradiate for 38min to obtain a lens; the remaining steps are the same as those in Example 2.
[0065] Comparative Example 3
[0066] The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: A. Pump the machine to a vacuum degree of 5.3×10 -3Pa, 400 ° C constant temperature for 3.8h, then lanthanum fluoride and magnesium fluoride coating, four layers of coating are sequentially coated, the bombardment voltage during coating is 810V negative high voltage, the bombardment time of each film is 13min, and the structure of the four-layer coating is 1.63H, 1.4121L, 0.833H, 0.9081L in sequence according to the coating sequence, wherein H is lanthanum fluoride and L is magnesium fluoride; B. After coating, annealing is performed in a fluorine gas atmosphere with a flow rate of 35Nm3 / h. The annealing is a secondary annealing. The temperature of the first annealing is 33 ° C and the time is 10min. The temperature of the second annealing is 83 ° C and the time is 28min. The remaining steps are the same as those in Example 2.
[0067] Effect example
[0068] Table 1 below shows the performance analysis results of the high-transmittance ultraviolet 193nm films of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.
[0069] Table 1
[0070] Single-side reflectivity (%) Double-sided light transmittance (%) Shedding situation (%) Example 1 0.020 ≥99.6 0 Example 2 0.019 ≥99.6 0 Example 3 0.021 ≥99.6 0 Comparative Example 1 0.247 ≥98.2 0 Comparative Example 2 0.579 ≥97.1 10 Comparative Example 3 0.228 ≥98.4 8
[0071] From the comparison of the experimental data of Example 2 and Comparative Example 1, it can be found that the present invention uses a vacuum coating method to alternately coat four layers of lanthanum fluoride and magnesium fluoride films on the surface of ultraviolet fused quartz in sequence, and annealing is performed in a fluorine gas atmosphere after coating. The presence of fluorine gas can make up for the problem of insufficient fluorine element in the fluoride film; from the comparison of the experimental data of Example 2 and Comparative Example 2, it can be found that annealing can release the internal stress inside the high-transmittance ultraviolet 193nm film, thereby reducing the stress level of the high-transmittance ultraviolet 193nm film, making up for the shortcomings of structural relaxation and poor environmental stability between the four layers of the film, improving its structural stability, and improving its compatibility with the ultraviolet fused quartz. English: From the comparison of the experimental data of Example 2 and Comparative Example 3, it can be found that when ultraviolet light external irradiation is applied during annealing, annealing and ultraviolet irradiation will provide sufficient energy for the lanthanum fluoride and magnesium fluoride atoms in the high-transmittance ultraviolet 193nm film to migrate and rearrange, thereby filling the gaps and defects in the film and increasing the density of the film. At the same time, ultraviolet light will optimize the microstructure and electronic state of the high-transmittance ultraviolet 193nm film, slow down the adsorption of water molecules and organic molecules by the film, further improve the density of the high-transmittance ultraviolet 193nm film, and improve the surface transmittance of the high-transmittance ultraviolet 193nm film and make it evenly distributed.
[0072] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a high-transmittance ultraviolet 193nm film, characterized in that: The method comprises the following preparation steps: (1) Preparation of substrate; (2) Coating: A. Pump the machine to a vacuum degree of 5.0~5..5×10 -3 Pa, 390~410℃ constant temperature for 3.5~4h, then lanthanum fluoride and magnesium fluoride coating, four layers of coating in sequence; B. After coating, annealing is performed in a fluorine atmosphere, and ultraviolet light is applied during annealing to obtain a lens; (3) The lenses are cleaned with organic solvents and then vacuum packed.
2. The method for preparing a high-transmittance ultraviolet 193nm film according to claim 1, characterized in that: The preparation of the substrate in step (1) comprises the following steps: a. Select UV grade fused silica JGS1 as the substrate; b. Remove dirt and dust from the substrate surface before coating; c. After the substrate is cleaned, it is heated to 400℃ in the machine.
3. The method for preparing a high-transmittance ultraviolet 193nm film according to claim 2, characterized in that: The surface of the substrate is cleaned by ultra-ultrasonic cleaning or manual wiping, with ether being used as the ultrasonic solvent, for 15 minutes.
4. The method for preparing a high-transmittance ultraviolet 193nm film according to claim 3, characterized in that: The power of the ultrasonic cleaning is 300-500W, and the ultrasonic frequency is 20kHz.
5. The method for preparing a high-transmittance ultraviolet 193nm film according to claim 1, characterized in that: In the step (2), the structures of the four-layer coating are 1.63H, 1.4121L, 0.833H, and 0.9081L in order of coating, wherein H is lanthanum fluoride and L is magnesium fluoride.
6. The method for preparing a high-transmittance ultraviolet 193nm film according to claim 1, characterized in that: During the coating process in step (2), the bombardment voltage is 800-820V negative high voltage, and the bombardment time for each layer of film is 10-15 minutes.
7. The method for preparing a high-transmittance ultraviolet 193nm film according to claim 1, characterized in that: The flow rate of the fluorine gas atmosphere in step (2) is 30-40 Nm 3 / h.
8. The method for preparing a high-transmittance ultraviolet 193nm film according to claim 1, characterized in that: The annealing in step (2) is a secondary annealing, wherein the temperature of the primary annealing is 30-35°C, the time is 8-13 min, and the temperature of the secondary annealing is 80-85°C, the time is 25-30 min.
9. The method for preparing a high-transmittance ultraviolet 193nm film according to claim 1, characterized in that: The ultraviolet light irradiation in step (2) is performed by using ultraviolet light with wavelengths of 185 nm and 254 nm until the annealing is completed.
10. The method for preparing a high-transmittance ultraviolet 193nm film according to claim 1, characterized in that: The organic solvent in step (3) is a mixture of acetone and methanol in a mass ratio of 1:1.